Prevalence and intensity of Trypanosoma sp. in wild swamp eels (Synbranchus bengalensis) marketed in Surabaya, Indonesia - Gunanti Mahasri; SETIAWAN KOESDARTO Koesdarto; KISMIYATI; DESI P. Wulan Sari; MUHAMMAD B. Santanumurti; IQYU W. KANDI Kandi; SELVI D.S. FITRI Savia Fitri; MUHAMAD AMIN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mahasri G, Koesdarto S, Kismiyati, Sari DPW, Santamurti MB, Kandi IW, Fitri SDS, Amin M. 2019. Prevalence and intensity of Trypanosoma sp. in wild swamp eels (Synbranchus bengalensis) marketed in Surabaya, Indonesia. Biodiversitas 20: 3262-3268. Trypanosoma sp. is parasitic protozoa, which can infect not only aquatic organisms but also humans. As the parasite considered a zoonosis disease, there has been a lot of concern about the presence of this parasite in aquaculture commodities. This research aimed to detect and determine the prevalence and intensity of Trypanosoma sp. infection in wild-caught swamp eels (Synbranchus bengalensis) marketed in Surabaya. A total of sixty swamp eels with 47.30±4.69 cm in length were collected from two different locations, Ambengan and Karah, Surabaya, East Java, Indonesia. The swamp eels were transported alive in two aerated plastic bags to the laboratory. The observed parameters were prevalence and intensity of Trypanosoma sp. in the eels’ blood, total erythrocyte counts and total differential leucocyte count (monocytes, lymphocytes, basophils, eosinophil, and neutrophil). The result showed that 7 of 30 (23%) wild-caught swam eels obtained from Ambengan and 9 of 30 eels (30%) collected from Karah were infected by Trypanosoma sp. The intensity of the parasite in eels collected from both locations was considered as moderate, 12.6 parasites/eel (Ambengan) and 5.9 parasites/eel (Karah). Additionally, hematology analysis indicated total erythrocytes count of blood in the infected eels from both locations were significantly lower than total erythrocytes of blood in the non-infected eels, p<0.05. Furthermore, hematology analysis indicated that the numbers of monocyte, lymphocyte, and neutrophil were significantly different than that of non-infected eels, P<0.05. Meanwhile, there was no significant difference in cell counts of basophils and eosinophil in the blood of infected and non-infected eels, p>0,05. These results demonstrate that swamp eels marketed in Surabaya were infected by Trypanosoma sp.